IMPLEMENTASI MEDIA PhET INTERACTIVE SIMULATIONS DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS IV SDN CIBABAT 4 PADA MATERI PECAHAN - Annisa Hidrayati; Asyifa Nur Jannah; Dea Amanda Putri; Ratna Sariningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Students' learning motivation for mathematics subjects on fractions tends to be low, which has an impact on student learning outcomes in class. Based on a survey at SDN Cibabat 4, there were students who were less interested in mathematics because it was considered difficult and unpleasant, so it is important to find ways that can increase students' learning motivation. This study aims to measure the learning motivation of mathematics on fractions of grade IV students at SDN Cibabat 4 using the interactive learning media PhET Interactive Simulation. The method used is descriptive quantitative, with collection through a questionnaire that includes six indicators of learning motivation. The subjects of this study were 27 grade IV students. The results of this study indicate that the use of PhET Interactive Simulations media significantly increases students' learning motivation, with an average percentage of motivation reaching 85.97% which is included in the